The International Security Environment Relevant to Pakistan (A Historical Perspective) - Ahmed Raza (Panoply Journal)
Pakistan came into existence amidst one of the most tumultuous times of the Cold War which suddenly escalated unprecedentedly in a manner where small, newly freed out of the colonial clutches, administratively fragile, economically unsustainable and, most of all, poorly led nations were caught in a sheer state of insecurity. Mentioning Pakistan precisely, it had not even emerged on the world map when prominent world leaders especially Pandit Nehru and other leaders from his party embarked upon an exhaustive campaign against its survival. Their propaganda hinged on a widely publicized conviction predominantly furthered by the western media which doubted Pakistan’s sustenance as a state rather they predicted its re-amalgamation into India due to its highly remote administrative infrastructure, absence of sound economy, and lack of pragmatic political leadership. This particular scenario was aggravated by almost the entire Muslim religious hierarchy in the sub-continent which fiercely opposed the creation of Pakistan, thus posing formidable existential threats to the newly born Muslim state.